Do governance and digital infrastructure support Asean-5 business growth? - Prestianawati, Silvi Asna; Setyanti, Axellina Muara (Digital Theory, Culture & Society, 2023)
ASEAN is one of the fastest growing economies in the world and is one of the five largest economies in the world after the US, EU, China, and Japan. ASEAN-5, the founding countries of Indonesia, Malaysia, the Philippines, Singapore, and Thailand ("ASEAN-5"). The ASEAN-5 countries represent 6% of the world's population with a GDP of US$2.75 trillion, growing at an average rate of 3.7% in 2019. With a supportive business climate, ASEAN-5 countries could be the preferred destinations for local or foreign companies to venture into new businesses. This study aims to analyze the impact of governance and digital infrastructure on new business growth in ASEAN-5 countries, using panel data regression approach. This study finds that profit tax, corruption perception, internet user, secure internet and access to electricity are significantly correlated with new business growth. Time to start a business is found to be insignificant but negatively correlated with growth, implying that more efficient bureaucracy promotes business growth.